2012
DOI: 10.7314/apjcp.2012.13.11.5415
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Personal Character on Quality of Life of Patients with Esophageal Cancer in North Henan Province and Influencing Factors

Abstract: The aim of this study was to investigate QoL (quality of life) of patients with esophageal cancer in northern Henan province, China, and to accurate evaluate and reflect the relationship between patient characteristics and QoL. In the high risk area of esophageal cancer in the north of Henan province, 735 patients with esophageal cancer were investigated. The Eysenck personality questionnaire (EPQ) and QoL were analyzed by using the questionnaire of general situation, EPQ, QLQ-C30 and QLQ-OES18. The effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Because previous studies have indicated that cancer patients' characteristics are associated with their disease‐related information needs and QoL , it is reasonable for us to postulate that patients who prefer to know their poor prognosis might reflect their optimistic characteristics or optimistic attitudes towards their diseases, which might contribute to their better QoL. However, further studies are needed to confirm this hypothesis.…”
Section: The Relationship Between Poor‐prognosis Disclosure Preferencmentioning
confidence: 92%
“…Because previous studies have indicated that cancer patients' characteristics are associated with their disease‐related information needs and QoL , it is reasonable for us to postulate that patients who prefer to know their poor prognosis might reflect their optimistic characteristics or optimistic attitudes towards their diseases, which might contribute to their better QoL. However, further studies are needed to confirm this hypothesis.…”
Section: The Relationship Between Poor‐prognosis Disclosure Preferencmentioning
confidence: 92%
“…reported EC significantly impaired Chinese patients' HRQoL in daily life after treatment; Lin et al . reported that personal characteristics were associated with patients' HRQoL in China . More studies from abroad focused on the impact of surgery or other treatments on the HRQoL of EC patients .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have measured the HRQoL directly in EC patients. 29 33 More studies from abroad focused on the impact of surgery or other treatments on the HRQoL of EC patients. [34][35][36] However, as far as we know, published empirical studies on the health condition effects and accurate data on the HRQoL utility values of EC and precancer in China remain scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Robust Quality of Life Questionnaires (QLQ) have been developed and validated in the past decades to measure the HRQL of oesophageal and gastric cancers (Hasegawa and Yoshikawa, 2010). Measuring HRQL in patients with cancer may help health professionals and caregivers to guide clinical decision making, to determine the efficacy and impact of cancer care and to identify the most troublesome symptoms and functional problems to alleviate patients to confront better with the disease (Ferrans, 2010), including those with oesophageal cancer (Lin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%